P PENGARUH PENGAWASAN DAN DISIPLIN KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN DI RUMAH SAKIT MEGA BUANA PALOPO - B, Sudirman; Uli, Nilawaty; Maidin, Achmad R. Muttaqien Al; Z, Zamli (PT.Mantaya Idea Batara, 2024)
Human resources (HR) are primary asset for the success of an organization or company, including in the context of hospitals. Proper management of HR will have a direct impact on operational effectiveness and efficiency, as well as the quality of services provided. Hospitals can ensure that each worker performs effectively in their roles with systematic and planned management. Ultimately, this leads to fulfilling the hospital's vision and mission while enhancing the quality of patient care. This study aims to assess the combined impact of supervision and work discipline on employee performance effectiveness. Research was carried out at Mega Buana Palopo Hospital, utilizing a qualitative research methodology with a descriptive analytical framework. The study involved 168 employees of Mega Buana Palopo Hospital as the target population. A total of 63 respondents participated in the study. In this research, the sampling technique was conducted using non-probability sampling with accidental sampling. Data analysis was processed using IBM SPSS Statistics 25. Results of the study show that significance values for supervisionX1) and work discipline (X2) are less than the alpha level (0.00 < 0.05), indicating that both supervision and work discipline significantly affect employee effectiveness at Mega Buana Palopo Hospital.